Pkm Meningkatkan Kemampuan Hardskill Guru Pembelajar Melalui Implementasi Macro Media Flash dan Video Pembelajaran Cooperative Learning Sebagai Pembelajaran Multimedia Dalam Bingkai PTK SMA/SMK Se Kabupaten Padang Pariaman - Susanti, Dessi; Armiati, Armiati; Dewi, Ika Parma; Rahmidani, Rose (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
The goal of this outreach activity is improving the ability of high school teachers hardskill and SMK Padang Pariaman Regency business management in terms of: 1) makes learning media with macro media flash, 2) makes RPP that contains model cooperative learning as an application of student centred learning (KTSP curriculum is the curriculum demands and 2013), 3) makes proposals PTK, 4) PTK with the application of the model of cooperative learning and learning media macro media flash 5) make reports and article PTK. The method of the approach being used is as follows: 1) for training and learning media making workshop with Macro Media Flash at once mengeksplorasikan and associate video learning cooperative Learning method using lectures, q & a, discussion, demonstration, granting, granting and tutorials, 2) for training and workshops make the RPP that contains the model of Cooperative Learning using the method using the method of lectures, q & a, discussion, granting, demonstrations, and tutorials, 3) for training and workshops making use of PTK proposal methods lectures, q & a, discussion, demonstration, granting, granting and tutorials, 4) for training and create reports and workshops Article PTK method using lectures, q & a, discussion, demonstration, granting, granting and tutorials, 5) For mentoring do PTK with the application of the model of cooperative learning and learning media macro media flash use methods tutorials. The result of the activities of this devotion is 1) it generates media learning with macro media flash by a large majority (85%) of teachers of subjects high school economics teacher and vocational areas of expertise (business management) of Padang Pariaman, 2) it generates RPP with the syntax of the model of cooperative learning (KTSP curriculum and curriculum demands 2013) by a large majority (85%) of teachers of subjects high school economics teacher and vocational areas of expertise (business management) of Padang Pariaman, 3) it generates a proposal by PTK most (85%) of teachers of subjects high school economics teacher and vocational areas of expertise (business management) of Padang Pariaman, 4) it generates PTK Reports by a large majority (85%) of economic subjects in high school teachers and teachers of vocational areas of expertise (business management Padang Pariaman Regency), 5) it generates article PTK by a large majority (85%) of teachers of subjects high school economics teacher and vocational areas of expertise (business management) of Padang Pariaman.